Urban Land Subsidence Characteristics and Their Relationship with Locations Liable to Waterlogging Based on SBAS-InSAR - LIU Huanyu; WU Zhen; YU Huanghao; CHEN Guangcheng; XIAO Yang; LI Kuang; LI Binquan (Renmin Zhujiang)
Under the background of global climate change, extreme rainstorm events occur frequently, and many cities have suffered from serious waterlogging, resulting in huge losses of people's lives and property. In order to analyze the relationship between urban land subsidence and waterlogging in coastal cities, this paper took Nansha District of Guangzhou as an example and selected 20 scenes of Sentinel-1 images from 2017 to 2023 as data sources. SBAS-InSAR technology was used to analyze land subsidence characteristics, and the correlation between the temporal subsidence of land waterlogging points and precipitation, water depth, and waterlogging duration was analyzed. The results show that: ① the average subsidence rate in Nansha District is 1.363 mm/a, and the subsidence area is mainly located in the river bank, construction area, and reclamation area. The average cumulative subsidence within six years is -10.05 mm, and the area with severe subsidence tends to expand. ② Regional seasonal heavy precipitation can alleviate land subsidence to a certain extent. The temporal subsidence process of sinking or stationary waterlogging points is synchronized with the seasonal variation of precipitation, and more obvious seasonal precipitation indicates a more gentle subsidence trend. ③The urbanization process and natural geographical conditions work together on the surface deformation. The waterlogging points caused by heavy rainfall in Nansha District mainly include local lowlands, overpass bottom, subway tunnel entrance, the unreasonable layout of the drainage pipeline system, or waterlogging that exceeds drainage capacity. According to the temporal evolution characteristics of surface deformation and the influence degree of water accumulation in each waterlogging point, the causes of waterlogging were traced respectively, which provided a reference for further prevention and control measures.